SISTEM INFORMASI PEMBAYARAN UANG SEKOLAH DENGAN MODEL MVC DAN MENGGUNAKAN NOTIFIKASI SMS GATEWAY - Dwi Cita Septia Candra; Lutfi Syarifullah; Muhammad Nur Faiz (Jurnal Sistem Informasi dan Informatika (Simika), 2021)
The Tuition Payment Information System was designed because at this time the payment of tuition at SMP Islam Cilacap still uses the general ledger, causing inaccuracies in payment data by employees (administrative). The purpose of this research is to help solve problems in the processing of tuition payment data, making payment data reports, searching payment data, knowing payment data information, and knowing the school money payment report. The system is designed using MVC (Model-View-Controller) architecture and SMS Gateway notifications as well as system development methods using System Development Life Cycle (SDLC) with Waterfall model. In addition, the system design uses PHP and HTML programming languages, database management is MySQL and uses the Laravel framework. Based on the results of the system test and the results of the questionnaire by 10 respondents that 14% stated enough, 44% stated well and 42% stated very well calculated by the calculation of the Likert scale of 86% entered the excellent qualification which means successful. So it can be concluded that this system can solve existing problems by facilitating the processing of payment data, assisting in the creation of school money payment reports, helping in speeding up the search for payment data, knowing the payment information of tuition without having to come to school, and knowing the payment data report quickly without having to go through a long recap process.